1994
DOI: 10.1017/s0022215100128580
|View full text |Cite
|
Sign up to set email alerts
|

The possible contributing factors for the success of steroid therapy in Bell's Palsy: a clinical and electrophysiological study

Abstract: Incomplete recovery from Bell's palsy was observed in some patients even after the intake of corticosteroids. This prospective study was performed on 160 patients with unilaterial nonrecurrent Bell's palsy in order to investigate the role of prednisolone on the prognosis of Bell's palsy. Ninety-three patients were given prednisolone tablets (1 mg/kg body wt/day up to 70 mg) for six successive days, then the dose was reduced gradually over the next four days. The remaining 67 patients were not given prednisolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 15 publications
0
23
1
7
Order By: Relevance
“…We graded one 14 nonrandomized, unmatched, controlled study with masked outcome assessments as class III. In this study, there were important confounding baseline differences between steroid-treated and non-steroid-treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We graded one 14 nonrandomized, unmatched, controlled study with masked outcome assessments as class III. In this study, there were important confounding baseline differences between steroid-treated and non-steroid-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients enrolled in these studies were treated within 1 week of onset of facial paralysis. The class III study 14 showed a nonsignificant trend of more benefit in patients who received steroids early (by day 1: RR 1.25; by day 2: RR 1.19; by day 3: RR 1.12).…”
Section: Table 2 Design Characteristics and Outcomes In Controlled Stmentioning
confidence: 94%
“…Other studies have shown the benefits of treatment with steroids; in one, patients with severe facial palsy showed a significant improvement after treatment within 24 hours (Shafshak 1994;Williamson 1996).…”
Section: Bell's Palsymentioning
confidence: 99%
“…While no single prognostic factor has been confirmed or refuted, research has suggested the following: degree of paresis and motor action potential value (Abraham-Inpijn et al 1987); serial minimal excitability of the facial nerve (Devi et al 1978); early intake of prednisolone (Shafshak et al 1994); the amplitude of evoked motor response obtained after 6 or more days of clinical paresis (Boongird and Vejjajiva 1978) and in children facial nerve latency was reported (Danselides et al 1992).…”
Section: Prognosismentioning
confidence: 99%